EVALUATION OF ULTRASONIC PULSE VELOCITY (UPV) FOR REINFORCED CONCRETE CORROSION - Almashakbeh, Yousef; Saleh, Eman (Journal of Applied Engineering Science, 2022)
This study was undertaken to evaluate the efficiency of the ultrasonic test for detecting reinforcement corrosion levels under varying conditions and to form a correlation between the ultrasonic pulse velocity (UPV) values and the flexural capacity of corroded beams. To establish this, several reinforced concrete beams were cast and subjected to an impressed current accelerated corrosion process. The severity of corrosion was then investigated using the UPV test and four-point loading test. The results showed that the UPV test values vary with the corrosion level of reinforcement in concrete beams. However, the degree of variation in UPV test values at different levels of corrosion does not permit a clear cut for the evaluation of corrosion severity, particularly at low levels of corrosion. The four-point testing of corroded beams showed that corrosion affects the flexural capacity and ductility of the beams. This effect was correlated in this study with the UPV test values. The correlation analysis showed that there exists a moderate to a high positive correlation between the UPV test values and flexural capacity of the beams while a low negative correlation between the UPV test values and ductility of the beams was observed.